Piloting a National Online Tutorial in Slavic Information Literacy: The LOTSE-Slavic Studies Project at Bochum University Library, Germany - Lapp, Erda (Nordic Journal of Information Literacy in Higher Education, 2010)
The presentation describes the Library Online Tour and Self-Paced Education (LOTSE) project for Slavic Studies (LOTSE-Slavistik) at Bochum University Library, Germany. LOTSE Slavic Studies is an open access online tutorial that provides German-speaking students and researchers an introduction to the most important resources in Slavic languages, literatures and cultures. The tutorial was developed at Ruhr University Bochum by the University Library in cooperation with the Slavic Department / Lotman Institute. It constitutes one module within a group of LOTSE modules (Business and Economics, Education, Engineering, Ethnology, Geography, History, Medicine, Music, Netherlands Studies, Philosophy, Psychology, Spanish Studies, Sociology, Theology). All LOTSE modules are embedded in larger subject portals, which are themselves under the umbrella of the online German national clearinghouse of subject portals, Vascoda. The pedagogically-designed LOTSE module Slavic Studies is intended primarily for students and can be used as a stand-alone e-learning tool or as an element of an integrated Slavic information literacy course. The presentation sets the broader historical and institutional context for the project, describes the content and layout of the LOTSE tutorial and summarizes how it has been used in recent undergraduate courses on Slavic information literacy.